Partial Discharges Identification and Localisation within Transformer Windings - Ali N.H.N.; Ariffin A.M.; Rapisarda P.; Lewin P.L. (Institute of Electrical and Electronics Engineers Inc., 2023)
Correlation methods; Mathematical morphology; Partial discharges; Winding; Automatic separations; Cross correlation methods; Extract informations; Localization of sources; Model transformers; Point of measurement; Relative performance; Waveform characteristics; Transformer windings